Investigating the Return of Goods in Supply Chain - Abanavaz, Fezzeh; Bafruei, Morteza Khakzar (International Review of Management and Marketing, 2020)
In the supply chain, the return of goods is of great importance. For different reasons, the flow of materials and goods is inevitable in the opposite direction of the chain. Therefore, dealing with the subject of the reverse logistics network and management and its leadership is effective and necessary. In this study, a two-level supply chain including suppliers and several retailers are studies with the possibility of return of goods in a problem of the newsvendor. First, to construct the initial model, the library method is used and then using mathematical methods to model determine the optimum order value and optimal supplier price and maximize the supply chain profit in a single-period model with a random demand market. It is also considering a case where the exchange of goods is justified in terms of a dearth of surplus-surplus and retailers unite. Keywords: supply chain, pricing chain and order value, return of goods, problem of the newsvendor JEL Classifications: C02 DOI: https://doi.org/10.32479/irmm.8313